Recent advances of high strength Mg-RE alloys: Alloy development, forming and application - Li, Yongfeng; Zhang, Ang; Li, Chuangming; Xie, Hecong; Jiang, Bin; Dong, Zhihua; Jin, Peipeng; Pan, Fusheng (Journal of materials research and technology, 2023)
To further expand the application of magnesium (Mg) alloys, development of the high strength Mg-rare earth (RE) alloys is strongly desired. The strength of the Mg alloys can be greatly improved through adding RE elements. This paper reviews the recent progress of the high-performance Mg-RE alloys, including alloy design, strengthening mechanism, forming processes, and applications. The review aims to provide references for designs, technologies, and applications of the Mg-RE alloys, which will contribute to further advancement of the Mg-RE alloys with excellent properties.